ClimateShot Global Action Agenda for Innovation in Agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security; Foreign, Commonwealth and Development Office (2021)
The ClimateShot Global Action Agenda for Innovation in Agriculture is the outcome of the campaign on ‘Transforming Agricultural Innovation for People, Nature and Climate’ co-chaired by CCAFS and the UK Foreign, Commonwealth & Development Office. It was launched at COP26 and received support from around 200 allies.